İznik keramiklerinin karakterizasyonu - Okyar, Füsun (Fen Bilimleri Enstitüsü, 1995)
İznik keramikleri' terimi, Osmanlı İmparatorluğu zamanında 14.-17.yüzyıllan kapsayan dönemde İznik'te üretilen her türlü seramik kap ve duvar çinileri için kullanılmıştır. Bu çalışmanın amacı, 1991 İznik Çini Fırınları kazısından ve 1970 öncesi kazı dönemlerinden çıkarılan farklı devirlere ait seramikleri, mikroyapı ve bileşim yönünden incelemek, üstün niteliğe sahip bu seramikleri kimyasal ve mineralojik açıdan karakterize etmektir. Çalışmada kırmızı hamurlu ilk Osmanlı keramiklerinden slip tekniği ile dekorlu keramikler ve Milet işi keramikler ile, beyaz hamurlu Mavi-beyaz, Şam ve Rodos işi keramik grublarma ait toplam 22 adet kazı numunesi incelenmiştir. İncelemeler esas olarak optik ve taramalı elektron mikroskobunda (JEOL-330) gerçekleştirilerek buluntuların hamur, sır ve astar bölgelerinin mikroanalizleri yapılmıştır. Kimyasal veriler ince-kesit çalışması ile desteklenerek, keramiklerin mineralojik kompozisyonu ve petrografik özellikleri tanımlanmıştır. İncelenen Slip tekniği ve Milet işi dekorlu keramiklerin kaba kırmızı hamurlu olduğu, içersinde henüz bir cam ağı oluşmadığı, buna karşılık kurşunca zengin inkluzyonlar içerdiği saptanmıştır. Kurşun-alkali bileşimindeki sırlarında kalay bulunmamaktadır. Diğer yandan beyaz hamurlu keramiklerde köşeli kuvars tanelerini saran cam ağında değişen oranlarda kurşun saptanmıştır. Kurşun-alkali bileşimindeki sır içersinde çoğu çözünmüş halde kalay oksit saptanmıştır. Elde edilen veriler tablolar, EDAX spektrumlan ve mikrograflar halinde verilmiştir. Petrografik analiz sonuçlan ikili diagramlar, tablolar ve çizimler halinde gösterilmiştir.

The term İznik ceramics is named after the pottery and tiles produced in İznik during the period between 14th and 17th centuries. Excavations in İznik have shown that the first Ottoman pottery is made from red clay covered with white slip. The technique is known to have been used by Selçuk potters in the early 13th century or even before and passed to the Ottomans. In the Ottoman ceramic sequence at İznik, the slip decorated monochrome ware was followed by a red-clay pottery of the type known as ' Miletus ware '. Towards the end of the 15 th century the red clay was replaced with a hard white clay. With this change we see the appearance of a new and magnificient type of a blue and white pottery closely resembling porcelain. So the development of İznik pottery starts with ' Blue and White ' ware, and continues through ' Golden Horn 'and 'Damascus wares ' to bole red ' Rhodos wares '. In this thesis, a selection of a group of İznik pottery sherds representing those different periods have been studied with chemical and mineralogical/petrographical methods. The glaze, slip and body characteristics and the microstructures of the sherds were determined. All of the sherds studied are selected from the material excavated in 'İznik Kiln Excavation 'in 1991 and from the excavation courses before 1970. In recent years most of the scientific studies about İznik ceramics appeared in the literature, have been carried out with the samples taken from the museums and private collections. vu In our experiments 22 sherds were examined. Samples were cut from the sherds with diamond discs to provide sections of the characteristic colourants. These samples were mounted in epoxy resin to provide sections through the glazes into the bodies. Fine polished sections of the sherds were examined in the stereomicroscope and their macrocharacteristics were detected. Then these sections were coated with carbon to be examined in the scanning electron microscope(JEOL-330). The phases present could be distinguished on the basis of their atomic number contrast by using the secondary and backscattered electron modes. Bulk semi-quantitative chemical compositions of the glaze, slip and body were determined using an energy dispersive X-ray spectrometer with light element detector (TN-5500 Tracor-Northern Z-Max 30) attached to the SEM. Accelerating voltage is 20 kV and the detection limit is 200 ppm. The SEM work was supplemented by the optical microscopy in order to complement the chemical information with petrographic data. A mineralogical and petrographical identification of İznik ceramics were done. Thin-section study was carried out to determine the mineral compositions and the minerals found in the samples were given with estimated modal compositions. The similarities were noted between various types and their overall petrographic character was evaluated. The sherds were examined in two main groups which differed in types of fabric as given below. The difference between the groups is also visible in colour ranging from a brick red to a white colour. 1. Red clay bodied ware (redware) a) Slip painted ware with monochrome glaze b) Miletus ware 2. Faience-bodied ware (whiteware) a) Blue-and-white ceramic ware b) Damascus ware c) Rhodos ware d) Polychrome slip painted ware The concluding remarks of the study are given below: RED CLAY BODIED WARE Slip painted ware and Miletus ware of İznik ceramics are made from earthenware clays which contain high iron (8-10% FeO). Their body contain 50% Si02, 15-17% A1203, 8-19% Fe203, 10% CaO and alkali. vw Examination of the samples showed that no detectable glassy phase has formed. The structure of the body was found to be very heterogeneous. A few alkali- rich glassy phase was found to be poorly developed and contained no lead. However some lead-rich and copper-rich inclusions were detected in the body that has similar composition of the glaze suggesting that the remnants of glaze or some fired ceramics(grog) containing glaze had been added to the body to improve the clay properties. The minerals present in the clay body are quartz, albite, biotite, hematite and epidote. The bodies also contain large, oriented pores, sometimes lined by or partly filled with secondary calcite. The red body is covered with a slip layer of quartz grains and clay mixture. Albite, quartz, and opaque minerals are detected in a glassy matrix. Chemical composition of the slip layer is 80% Si02, 7% CaO, 9 %A1203, FeO <1 % and alkali. The lead detected in the slip layer comes from the lead glaze extending into the slip. In the interaction zone between the glaze and the slip layer the presence of CaS04 particles were detected. The glaze over the slip is of the lead-alkali-silicate type. Lead content of the glaze is found to be 25-30% over the blue-white decorated faces. The slip decorated sherds coloured with iron yellow-brown pigments and the copper green coloured back faces are covered with a high lead glaze (50% PbO). No trace of tin is detected in the glaze layer. The decoration is of the underglaze type being applied to the surface of the sup using a range of mineral-based colourants. Depending on the decoration colour, the glaze contains differing amounts of CoO(0.2-3.4%), NiO(0.2-1.7%) CuO(0.2- 2.2%), FeO(l. 2-2.9%), MnO(1.9-5.9%) and ZnO(0.5-1.0%). In addition, a presence of 0.1-0.2% Cr2C>3 is detected in the contour regions. Antimony is also occasionally observed in the glaze. FAIENCE-BODIED WARE The İznik whiteware bodies consist of 80% quartz and 20% heterogeneous glass matrix that bonds the quartz particles together. The glass phase contains variable amounts of Na20, CaO, PbO and P205. This phase can be accepted as a clay and frit mixture. Lead-calcium-silicate and phosphorous rich areas are detected in this glassy network. IX The composition of the glass network in the body is found to be 68-76%Si02, 2-5%Al203, 7-8%Na20, l-2%MgO, 1.5-3%K20, 3-5%CaO,3-5%PbO, 0.5%P2O5, 0.7-3%FeO. The calcium and phosphorus rich areas detected in the body suggest that bone ash was added to the body mixture. Because of the angular quartz grains and the low melting point of the glass phase, the firing temperature for the whitewares is probably less than 1000° C. The slip layer of the quartz-frit type is produced from a purer and finer textured quartz. The application of this layer gives a fully white appearance and minimize the use of the expensive, pure and fine textured quartz in the body. The slip layer shows a mosaic structure of quartz crystals, microcrystalline minerals and some opaque particles under the transmitted light. Quartz content of the slip layer is 80- 90% and iron oxide content is less than 1%. So this very fine textured and very low iron quartz-clay-frit mixture provides an excellent white base for the underglaze decoration. The glaze is again of lead-alkali type with a medium lead content (30- 40%PbO) and contains significant amount of tin oxide (2 -12%). Majority of tin is in solution and there are only occasional tin oxide particles in the glaze layer detected as agglomerated white crystals Microscopic examinations of the sherds showed that the thickness of the transparent glaze layer is 70-400u,m. There is a glaze-slip interaction layer of 70-250um formed by the glaze extention into the slip whereas the thickness of the fine textured quartz-frit slip is «500 um. The colourant for turquoise is copper oxide, that for blue is cobalt oxide, and that for the black lines is an iron chromite spinel mineral. The chromite colourant did not dissolve in the glaze and remained as small angular particles. The colourant for bole red is a mixture of very fine particles of hematite (less than lum) and quartz (lOum). The bulk composition of the bright red colour of İznik ceramics was found to be 83-88%Si02, 4-9%FeO, 3-4%Na20+K20, l%PbO, l%CaO, 0.5-l%Al2O3, 0.1-0.4%MgO. This high concentration of Si02 and FeO of the pigment leads to a lens-shaped relief of the glaze layer. In summary, the microstructures and chemical composition of the sherds examined indicate that in all the different whitewares of İznik ceramics the same technology was employed in their production. The İznik body differs from all other known islamic fritware traditions in using an alkali-lead, rather than alkali-lime frit. The body is a mixture of ground quartz, white clay and lead frit. Glazes are of the medium lead alkali type and contain dissolved tin oxide and mineral oxides that have been applied as colourants over the slip layer.
Characterization of İznik ceramics
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1995.
Keywords: Bursa-İznik; Seramikler; Bursa-İznik; Ceramics